Assessing endocrine disruption in freshwater fish species from a "hotspot" for estrogenic activity in sediment. (February 2020) - Müller, Anne-Katrin; Markert, Nele; Leser, Katharina; Kämpfer, David; Crawford, Sarah E.; Schäffer, Andreas; Segner, Helmut; Hollert, Henner
Abstract: Little is known about sediment-bound exposure of fish to endocrine disrupting chemicals (EDC) under field conditions. This study aimed to investigate potential routes of EDC exposure to fish and whether sediment-bound contaminants contribute towards exposure in fish. Tench ( Tinca tinca ) and roach ( Rutilus rutilus ) as a benthic and pelagic living fish species, respectively, were sampled at the Luppe River, previously described as a "hotspot" for accumulation of EDC in sediment. A field reference site, the Laucha River, additionally to fish from a commercial fish farm as reference were studied. Blackworms, Lumbriculus variegatus, which are a source of prey for fish, were exposed to sediment of the Luppe River and estrogenic activity of worm tissue was investigated using in vitro bioassays. A 153-fold greater estrogenic activity was measured using in vitro bioassays in sediment of the Luppe River compared the Laucha River. Nonylphenol (NP; 22 mg/kg) was previously identified as one of the main drivers of estrogenic activity in Luppe sediment. Estrogenic activity of Luppe exposed worm tissue (14 ng 17β-estradiol equivalents/mg) indicated that food might act as secondary source to EDCs. While there were no differences in concentrations of NP in plasma of tench from the Luppe and Laucha, vitellogenin, a biomarker for exposure to EDCs, was induced in male tench and roach from the Luppe River compared to both the Laucha and cultured fish by a factor of 264 and 90, respectively. However, no histological alterations in testis of these fish were observed. Our findings suggest that sediments substantially contribute to the overall EDC exposure of both benthic and pelagic fish but that the exposure did not impact gonad status of the fish. Graphical abstract: Image 106 Highlights: Potential sources of EDC exposure: profiling in sediment, water and fish. Biomarker induction in male fish from a hotspot for EDC contamination in sediment. Evaluation of dietary exposure of fish to sediment-bound EDCs.